A STUDY ON IMPACT OF CUSTOMER EXPERIENCE AND ENVIRONMENT CONCERN ON CUSTOMER ENGAGEMENT TOWARDS ELECTRIC BIKES WITH SPECIAL REFERENCE TO HYDERABAD CITY - Tharimala, Dr. ShesadriKiran; Dr. PerikalaUmapathi (The journal of contemporary issues in business and government, 2022)
Since a decade the society is witnessing the tremendous change in awareness, preference and usage of products and services by the customer. The environmental concern of the customers is igniting an idea of using eco-friendly products. So, in connection to it, this paper is mainly focused on exploring the impact of customer experience and environmental concern on customer engagement towards electric vehicles. This study stands unique among the relevant literature in the same area by adopting environmental concern as one of the independent variables. The people who are using e-bikes were considered as population for the study. The sample had been drawn from Hyderabad city. Further, factor analysis and regression were adopted to analyse the data. The results of the study indicate that the two independent variables were proved to have significant positive effect on customer engagement. The findings of the study provide more valuable insights to manufacturers of electric vehicles.